THE ROLE OF THE PUBLIC PROSECUTOR IN CRIMINAL PROCEEDINGS – THE POLISH PERSPECTIVE - Bojanowski, Tomasz (International Journal of Legal and Social Order, 2026)
The subject of the presentation will be an analysis of the role of the prosecutor in Polish criminal proceedings. The prosecutor’s activity is determined by the principles governing the prosecution service, an institution that has undergone significant organizational changes in recent years and continues to evolve. The author will begin with an introduction presenting the constitutional and systemic position of the prosecutor within the framework of the bodies responsible for the protection of the rule of law and within the system of criminal procedure authorities. It will then move on to discuss the prosecutor’s role in criminal proceedings, identifying three main functions: (1) as the authority conducting preparatory proceedings, (2) as the public prosecutor, and (3) as the guardian of the public interest. Each of these roles will be discussed in greater detail. In connection with the ongoing debate on the prosecutor as the guardian of the public interest (and the rule of law), the author will also offer de lege ferenda remarks.